A preliminary study of dopamine D2/3 receptor availability and social status in healthy and cocaine dependent humans imaged with [11C](+)PHNO. (1st September 2015) - Matuskey, David; Gaiser, Edward C.; Gallezot, Jean-Dominique; Angarita, Gustavo A.; Pittman, Brian; Nabulsi, Nabeel; Ropchan, Jim; MaCleod, Paige; Cosgrove, Kelly P.; Ding, Yu-Shin; Potenza, Marc N.; Carson, Richard E.; et al.
Highlights: This paper examines social status and D2/3 R availability in humans. Healthy and cocaine dependent individuals were studied with the tracer [ 11 C](+)PHNO. Inverse associations between social status and D2/3 R availability were observed. These areas included D3 R rich brain reward areas in both groups. These findings demonstrate a novel relationship between social status and D2/3 R. Abstract: Background: Previous work in healthy non-human primates and humans has shown that social status correlates positively with dopamine 2/3 receptor (D2/3 R) availability imaged with antagonist radioligands and positron emission tomography (PET). Further work in non-human primates suggests that this relationship is disrupted by chronic cocaine administration. This exploratory study examined the relationship between social status and D2/3 R availability in healthy (HH) and cocaine dependent (CD) humans using the D3 -preferring, agonist radioligand, [ 11 C](+)PHNO. Methods: Sixteen HH and sixteen CD individuals completed the Barratt Simplified Measure of Social Status (BSMSS) and underwent [ 11 C](+)PHNO scanning to measure regional brain D2/3 R binding potentials ( BP ND ). Correlations between BP ND and BSMSS scores were then assessed within each group. Results: Within HH and CD groups, inverse associations between BSMSS score and BP ND were observed in the substantia nigra/ventral tegmental area (SN/VTA) and the ventral striatum, and for the CD group alone, the amygdala. After adjusting for body mass index and age, negative correlations remained significant in the SN/VTA for HH and in the amygdala for CD subjects. Conclusion: These preliminary data utilizing a dopamine agonist tracer demonstrate, for the first time, an inverse association between social status and D2/3 R availability in the D3 R rich extrastriatal regions of HH and CD humans.